Business and Human Rights : Emerging Challenges, Issues, and Trends - Andreas R. Ziegler; Damiano Canapa; Maria Izabel Cardozo (Brill | Nijhoff, 2025)
The open access publication of this book has been published with the support of the Swiss National Science Foundation. This book explores the interface of Business and Human Rights with other practice areas, such as antitrust, arbitration, artificial intelligence, investment law, finance, private international law, professional ethics, labor law, sports law, venture capital, among others. It presents contributions from a diverse and international group of academics, researchers, and practitioners in Europe, Asia, and South America. It also includes the International Bar Association's Updated Guidance Note on Business and Human Rights for lawyers, which represents a relevant policy development in the intersection of Business and Human Rights and professional legal ethics.